2019
DOI: 10.1007/s11606-019-05259-1
|View full text |Cite
|
Sign up to set email alerts
|

Secure Messaging with Physicians by Proxies for Patients with Diabetes: Findings from the ECLIPPSE Study

Abstract: BACKGROUND: Little is known about patients who have caregiver proxies communicate with healthcare providers via portal secure messaging (SM). Since proxy portal use is often informal (e.g., sharing patient accounts), novel methods are needed to estimate the prevalence of proxyauthored SMs. OBJECTIVE: (1) Develop an algorithm to identify proxyauthored SMs, (2) apply this algorithm to estimate predicted proxy SM (PPSM) prevalence among patients with diabetes, and (3) explore patient characteristics associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…For the current analyses, only those SMs sent between patients and primary care physicians were included. We excluded all SMs from patients who did not have matching DISTANCE survey data, were written in a language other than English, and were written by proxy caregivers ( 61 ). The total patient sample in the ECLIPPSE Study was N = 9530; the total physician sample was N = 1165.…”
Section: Methodsmentioning
confidence: 99%
“…For the current analyses, only those SMs sent between patients and primary care physicians were included. We excluded all SMs from patients who did not have matching DISTANCE survey data, were written in a language other than English, and were written by proxy caregivers ( 61 ). The total patient sample in the ECLIPPSE Study was N = 9530; the total physician sample was N = 1165.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies characterizing the use of the patient portal suggest that low engagement with the patient portal for certain populations, such as older adults, could be attributed to technology barriers or to the possibility that family caregivers are using the patient portal on their behalf [6,7]. Although some caregivers have formal proxy access to their care recipient's portal (with estimates at less than 5%), some literature suggests that 25% to 50% of proxies informally use their care recipient's portal [13][14][15]. By offering caregivers log-in credentials for informal proxy access, patients may share more health information than intended or desired [16].…”
Section: Introductionmentioning
confidence: 99%
“…15 A HL scoring rubric was used to assess holistically the HL of the patients based on the content of their SMs, adapting an established rubric used to score the writing abilities of high school students entering college. 15,26 An ordinal scale ranging from 1 to 6 assessed the extent to which patients' SMs demonstrated mastery of written English, organization, and focus, and a varied, accurate, and appropriate health vocabulary to enable clear access to the health-related content and ideas the patient wanted to express to their physician. 15 Because of limited relevance to the construct of HL, we removed parts of the rubric related to length, developing point of views, and discourse-related elements important in argumentative writing including the use of examples, reason, and evidence.…”
Section: Methodsmentioning
confidence: 99%
“…15 Prior research that has indicated that lexical features related to word choice, discourse features, and sentence structure are strong predictors of writing quality. [26][27][28] To capture these features, we used three NLP tools that derive linguistic features related to lexical sophistication, text cohesion, and syntactic complexity, which we briefly describe here. These included: (1) the Tool for the Automatic Analysis of Lexical Sophistication (TAALES), [29][30] a computational tool that incorporates over 100 classic and newly developed indices of lexical sophistication.…”
Section: Methodsmentioning
confidence: 99%